Effects of biophilic design-based sports facilities on exercise continuation intention: mediating effects of exercise immersion and moderating effect of environmental awareness - Lee, Kyongmin; Park, Sung-Jun (Frontiers in Psychology, 2025)
The purpose of this study is to empirically analyze how biophilic design elements in sports facilities influence exercise immersion and the intention to continue exercising. Specifically, the study explores the psychological mechanisms underlying this relationship by testing the mediating effect of exercise immersion and the moderating effect of environmental awareness. A structured survey was administered to 200 physical education majors in Busan and Daegu, South Korea. Correlation analysis, regression analysis, and both mediating and moderating effect analysis were performed to confirm the relationships among the key variables. The findings indicate that biophilic design components positively affect both cognitive and behavioral immersion, and that exercise immersion significantly predicts the intention to continue exercising. Moreover, the psychological/physical effects and indirect natural elements partially mediated the relationship between biophilic design and exercise continuation intention through exercise immersion. Specifically, the mediation analysis revealed that, for psychological/physical effects, the indirect pathway via cognitive immersion accounted for 26.9% of the total effect and via behavioral immersion for 51.1%. For indirect natural elements, the proportions were 20.8% (cognitive immersion) and 25.9% (behavioral immersion). These results indicate substantial, though not exclusive, mediation effects. On the other hand, environmental awareness did not exhibit a statistically significant moderating effect. These findings highlight the psychological mechanisms through which spatial design in sports facilities fosters deeper engagement and sustained participation. The study suggests that strategically incorporating biophilic design elements may enhance user experience and promote long-term exercise participation. This research contributes both theoretically and practically to the development of sustainable sports facilities through an integrative perspective combining sports psychology and environmental design.